Microstructure and pore structure of polymer-cement composite joint sealants - Chuanxin Lou (Nature Portfolio, 2021)
Abstract Utilizing methods such as scanning electron microscopy observation and mercury intrusion porosimetry, this paper investigates the basic microstructure and pore structure properties of polymer-cement composite joint sealants for pavements, and analyzes the effects and rules of various material types, ratio parameters and processing conditions. Further, the fractal characteristics and variation rules of pore size distribution are investigated for the joint sealants by introducing the fractal theory. The results show that changes in material type, ratio parameter and processing condition produce insignificant effects on the basic microstructure properties and configuration of joint sealants, with effects reflected primarily in the change of sealant pore structure. Measures like increasing the powder-liquid ratio and cement ratio, blending with sulphoaluminate cement or mica powder, adding latex powder or coupling agent, cold drawing and hot pressing, as well as ultraviolet irradiation treatment are all capable of reducing the total pore volume of joint sealants and refining their pore structure. In contrast, opposite effects are yielded when low-grade cement is used, styrene-acrylic emulsion is blended, or plasticizer is added. Additionally, after blending with talc powder or adding carbon fiber additive, the total pore volume of joint sealants remains basically unchanged or reduced, despite the coarsened pore structure. The total pore volume of joint sealants increases after wet–dry cycling treatment, while no obvious change in the pore size distribution is observed. Pore size distribution of the studied joint sealants presents distinct fractal characteristics, and the corresponding fractal dimension of pore surface area ranges between 2.6 and 2.8.